Efficient Removal of Methyl Orange from Water onto PVC/Bentonite Membranes: Experimental Validation and COMSOL Multiphysics - Souhıla Khellaf (International Journal of Intelligent Systems and Applications in Engineering, 2024)
Nowadays, the treatment of domestic and industrial wastewater is a very important topic in environmental protection. Reuse of this water is one of the possibilities already implemented. A rapidly developing process in this area is membrane filtration. Membranes based on polymer materials are generally employed in the purification of wastewater resulting from the accumulation of dyes in industries such as textiles, paper, and others. In this regard, membranes using polyvinyl chloride (PVC) added to Bentonite, which is natural clay obtained from the Roussel deposit (Maghnia, Algeria) were prepared. Bentonite was chosen for its remarkable ion adsorption properties and its incorporation at different ratios improves the membrane’s efficacy for water treatment purposes. The filtrates collected were studied using UV-Vis spectroscopy. This technique allowed us to estimate the removal capacity of organic dye, methyl orange, from our membranes. The results demonstrated that our newly prepared materials with higher Bentonite content exhibited a better depollution efficiency and, consequently, higher capacity adsorption for methyl orange. This is indubitably attributed to the porous structure of Bentonite. Thus, these membranes represent the current best alternative to known separation techniques. The finite element method-based software COMSOL Multiphysics has been used to investigate filtration processes in the model system. Finally, the numerical results of the proposed model are compared with the available experimental data and that represent good agreement.